(untitled) - Gunning, Brian E.S. (Boston, 1996)
Contents: Microscopy of plant cells; nucleus; vacuoles; mitochondria; nucleic acids in mitochondria and plastids; plant reproduction; the plant as a multicellular organism.
Keywords: Cell biology,Molecular biology,Tế bào sinh học,Mô sinh vật